2014
DOI: 10.2147/ijn.s59661
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effect of magnetic iron oxide nanoparticles synthesized via seaweed aqueous extract

Abstract: Magnetic iron oxide nanoparticles (Fe 3 O 4 MNPs) are among the most useful metal nanoparticles for multiple applications across a broad spectrum in the biomedical field, including the diagnosis and treatment of cancer. In previous work, we synthesized and characterized Fe 3 O 4 MNPs using a simple, rapid, safe, efficient, one-step green method involving reduction of ferric chloride solution using brown seaweed ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
110
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(133 citation statements)
references
References 29 publications
(26 reference statements)
15
110
0
Order By: Relevance
“…In MOLT-4 cells, treatment with Pd@W.tea NPs significantly increased the activities of caspase-3 and -9 (Table 6). Caspase pathway-mediated apoptosis seems to be the common mode of cell death instituted by NPs; for example, with zerumbone-loaded nanostructured lipid carriers and magnetic iron oxide NPs on Jurkat cells, 51 amine-modified polystyrene NPs on astrocytoma cells, 52 and nickel-zinc ferrite NPs on the HepG2, HT29, and MCF-7 cell lines. 53 …”
Section: Phosphatidylserine Translocationmentioning
confidence: 99%
“…In MOLT-4 cells, treatment with Pd@W.tea NPs significantly increased the activities of caspase-3 and -9 (Table 6). Caspase pathway-mediated apoptosis seems to be the common mode of cell death instituted by NPs; for example, with zerumbone-loaded nanostructured lipid carriers and magnetic iron oxide NPs on Jurkat cells, 51 amine-modified polystyrene NPs on astrocytoma cells, 52 and nickel-zinc ferrite NPs on the HepG2, HT29, and MCF-7 cell lines. 53 …”
Section: Phosphatidylserine Translocationmentioning
confidence: 99%
“…38 SPIONs have already been synthesized via the green route by various investigators. [20][21][22][23][24]39,40 However, use of peel biomass has not been reported for the MW-assisted green synthesis of SPIONs with a narrow size distribution, increased stability, and multifunctionality, crucial for biokinetics and biodistribution in developing theranostics. The scheme of this work is described in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19] Consequently, numerous efforts have been focused on refining the properties of metal NPs through modification of their synthesis methods from conventional methods to green ones. Some of these include the use of seaweed, 20 tea, 21,22 as well as peel extracts of plantain, 23 banana, 24 and orange. 25 Although biocompatibility has been achieved in such reports, there is a dire need for the successful surface engineering of such biologically safer NPs to enable a variety of biomedical and other industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent in vitro studies by Namvar et al using the derived Fe 3 O 4 nanoparticles evaluated their cytotoxicity, cellular responses, and anticancer activity towards human cell lines for leukemia, breast cancer, cervical cancer, and liver cancer. The in vitro studies found the accumulation of Fe 3 O 4 nanoparticles in treated cells tended to promote cell apoptosis and confirmed their potential use in the treatment of cancer [143].…”
Section: Metal Oxide Nanoparticlesmentioning
confidence: 55%